Psikologi Kompetitif Individu Untuk Meningkatkan Kualitas Taruna - Romanda Annas Amrullah; Kristin Anita Indriyani; Upik Suryandari (Dinamika Bahari, 2022)
Competitive advantage can be said to be a prerequisite for success for cadets. Education is an effort to improve the quality of each individual directly or indirectly. With the developments that occur in the world of education that requires lecturers and cadets to have a creative, innovative and most importantly competitive attitude. This study was written to discuss the development of individual competitive psychology in order to improve the quality of cadets. The purpose of this study was to investigate the factors that influence the quality of seafarers by using the Individual Competitive Psychology model. This study conducted a survey of 120 prospective cadets and cadets who were currently studying at official universities and government-owned nurseries. This self-administered questionnaire includes questions about the quality of prospective cadets and cadets with regard to morals, moral decisions and Bourdieu's sociological theory. The quality of prospective cadets and cadets is influenced by moral and psychological decisions. This study shows that the moral and psychological decisions of cadets and prospective cadets are important to score in the input process as well as to form the mentality of cadets in output so it is very important to have a competitive attitude for cadets because a cadet who is very competitive has the opportunity to see certain situations as competition.